PERSEPSI SISWA TENTANG PENGELOLAAN PERPUSTAKAAN DI SMA NEGERI 2 LUBUK BASUNG - Fatma Fitriani (Jurnal Bahana Manajemen Pendidikan, 2014)
The goal of this research are to see information about the students perception about management of library in SMA Negeri 2 Lubuk Basung. The kind of the research is descriptive. The population is 1030 students in SMA Negeri 2 Lubuk Basung and the sample is 105 people that taken by claster random sampling. The instrument of this research is question with likert scale models  that had tested for validity and reliability. Data analyzed using mean score. The result of this research are the students perception about management of library in SMA Negeri 2 Lubuk Basung stay in good category with mean score 3,64. Key word: Management of library